Association of long-term PM2.5 exposure with traditional and novel lipid measures related to cardiovascular disease risk - McGuinn, Laura A.; Schneider, Alexandra; McGarrah, Robert W.; Ward-Caviness, Cavin; Neas, Lucas M.; Di, Qian; Schwartz, Joel; Hauser, Elizabeth R.; Kraus, William E.; Cascio, Wayne E.; Diaz-Sanchez, David; Devlin, Robert B. (Environment international, 2019)
Fine particulate matter (PM2.5) exposure is associated with increased morbidity and mortality, particularly for cardiovascular disease. The association between long-term exposure to PM2.5 and measures of lipoprotein subfractions remains unclear. Therefore, we examined associations between long-term PM2.5 exposure and traditional and novel lipoprotein measures in a cardiac catheterization cohort in North Carolina. This cross-sectional study included 6587 patients who had visited Duke University for a cardiac catheterization between 2001 and 2010 and resided in North Carolina. We used estimates of daily PM2.5 concentrations on a 1 km-grid based on satellite measurements. PM2.5 predictions were matched to the address of each patient and averaged for the year prior to catheterization date. Serum lipids included HDL, LDL, and triglyceride-rich particle, and apolipoprotein B concentrations (HDL-P, LDL-P, TRL-P, and apoB, respectively). Linear and quantile regression models were used to estimate change in lipoprotein levels with each μg/m3 increase in annual average PM2.5. Models were adjusted for age, sex, race/ethnicity, history of smoking, area-level education, urban/rural status, body mass index, and diabetes. For a 1-μg/m3 increment in PM2.5 exposure, we observed increases in total and small LDL-P, LDL-C, TRL-P, apoB, total cholesterol, and triglycerides. The percent change from the mean outcome level was 2.00% (95% CI: 1.38%, 2.64%) for total LDL-P and 2.25% (95% CI: 1.43%, 3.06%) for small LDL-P. Among this sample of cardiac catheterization patients residing in North Carolina, long-term PM2.5 exposure was associated with increases in several lipoprotein concentrations. This abstract does not necessarily reflect U.S. EPA policy. •We examined associations between long-term PM2.5 exposure and lipoprotein measures.•Associations were present for several measures including total and small LDL-P.•Quantile regression results showed an increasing trend for percentiles of LDL.